Parents' decision making needs regarding circumcision of male newborns. - Taylor-Clapp, Susan. (University of Ottawa (Canada), 2001)
This study, conducted as a needs assessment, was guided by O'Connor's Decision Support Framework (DSF). The DSF describes a process of providing to both parents and practitioners decision support by identifying the sub-optimal determinants of the decision. The objectives of the study were to describe the decision making needs of parents making choices about neonatal male circumcision and the needs of prenatal instructors who inform parents about options. The study design was across-sectional survey of 88 mothers and 67 fathers and 10 prenatal instructors. Structured questionnaires were used, eliciting variables based on the DSF, such as: the perception of the decision; perception of others regarding the decision; resources to make the decision; and participant characteristics. Although all instructors stated that circumcision was discussed, the content of the discussion varied according to the instructor's experience and perception of the decision. Most instructors (9/10) believed parents lacked both information about options and chances of the benefits and risks. Few of the instructors (2/10) saw their role as instrumental in the decision. (Abstract shortened by UMI.)
Keywords: Health Sciences, Nursing.